HUBUNGAN MOTIVASI KADER POSYANDU DENGAN UPAYA PENINGKATAN KUNJUNGAN BALITA DI WILAYAH KERJA PUSKESMAS PAMATANG SILIMAHUTA - Maria M U Girsang; Siti Marlina (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2019)
Motivation is defined as strength, encouragement, needs, enthusiasm, pressure, or psychological mechanisms that encourage someone or a group of people to achieve certain achievements in accordance with what people want. Integrated service post is one form of health services organized by the community for the community with technical support from local health workers. The purpose of this study was to determine the relationship between the motivation of integrated service postcadres and efforts to increase children under five year visits in the area in the Pamatang Silimahuta Community Health Center work area. The sample was 73 respondents using random sampling techniques. The design of this study used analytic survey research, using the Cross Sectional approach and data collected from respondents using questionnaire sheets. The results showed a relationship between integrated service post cadre motivation and efforts to increase children under five year visits in the Pamatang Silimahuta Community Health Center work area with p value = 0.007 smaller than 0.05. It was suggested to the relevant parties to give awards to cadres so that it could motivate integrated service postcadres to be more active so that it can increase children under five year visit to the integrated service post.